Does programmed intermittent epidural bolus improve childbirth conditions of nulliparous women compared with patient-controlled epidural analgesia?: A multicentre, randomised, controlled, triple-blind study. Issue 10 (October 2019) - Morau, Estelle; Jaillet, Malaury; Storme, Brigitte; Nogue, Erika; Bonnin, Martine; Chassard, Dominique; Benhamou, Dan; Nagot, Nicolas; Dadure, Christophe
Abstract : BACKGROUND: Epidural analgesia may change the mechanics of childbirth. These changes are related to the concentration of the local anaesthetic used epidurally but probably also to its mode of delivery into the epidural space. OBJECTIVE: To determine whether the administration of programmed intermittent epidural boluses (PIEB) improves the mechanics of second-stage labour compared with patient-controlled epidural analgesia (PCEA) with a background infusion. DESIGN: A randomised, controlled, triple-blind study. SETTING: Multicentre study including four level III maternity units, January 2014 until June 2016. PATIENTS: A total of 298 nulliparous patients in spontaneous labour were randomised to a PIEB or PCEA group. INTERVENTION: After epidural initiation with 15 ml of 0.1% levobupivacaine containing 10 μg of sufentanil, patients received either an hourly bolus of 8 ml (PIEB) or a continuous rate infusion of 8 ml h −1 (PCEA): the drug mixture used was levobupivacaine 0.1% and sufentanil 0.36 μg ml −1 . MAIN OUTCOME MEASURES: The primary outcome was a composite endpoint of objective labour events: a posterior occiput position in the second stage, an occiput position at birth, waiting time at full cervical dilatation before active maternal pushing more than 3 h, maternal active pushing duration more than 40 min, and foetal heart rate alterations. Vaginal instrumental delivery rates, analgesia and motor blockade scores were also recorded. RESULTS: From the 298 patients randomised, data from 249 (124 PIEB, 125 PCEA) were analysed. No difference was found in the primary outcome: 48.0% (PIEB) and 45.5% (PCEA) of patients, P = 0.70. In addition, no difference was observed between the groups for each of the individual events of the composite endpoint, nor in the instrumental vaginal delivery rate, nor in the degree of motor blockade. Despite an equivalent volume of medication in the groups, a significantly higher analgesia score at full dilatation was observed in the PIEB group, odds-ratio = 1.9 (95% confidence interval, 1.0 to 3.5), P = 0.04. CONCLUSION: The mechanics of the second stage did not differ whether PIEB or PCEA was used. Analgesic conditions appeared to be superior with PIEB, especially at full dilation. TRIAL REGISTRATION: NCT01856166.